2016
DOI: 10.3109/0284186x.2016.1170197
|View full text |Cite
|
Sign up to set email alerts
|

Early 18F-FDG-PET/CT as a predictive marker for treatment response and survival in patients with metastatic colorectal cancer treated with irinotecan and cetuximab

Abstract: With both EORTC criteria and PERCIST, early reduction in FDG uptake was predictive of a later partial metabolic and partial radiologic response to treatment. It was also predictive of significantly longer survival of early metabolic responders compared to non-responders. However, the sensitivities and specificities were not high enough to support clinical routine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Although there are several studies that have evaluated the role of SUVmax as a predictive marker in such patients, only a few studies have examined the prognostic role of PET/ CT parameters in relation to overall survival and progression-free survival in patients with colorectal cancer (4,5). However, the results of studies investigating the role of PET/CT in the evaluation of treatments have revealed certain potential for Clinical Science the formation of a prognostic model that would include SUVmax along with classical prognostic markers (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several studies that have evaluated the role of SUVmax as a predictive marker in such patients, only a few studies have examined the prognostic role of PET/ CT parameters in relation to overall survival and progression-free survival in patients with colorectal cancer (4,5). However, the results of studies investigating the role of PET/CT in the evaluation of treatments have revealed certain potential for Clinical Science the formation of a prognostic model that would include SUVmax along with classical prognostic markers (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In older series on mCRC patients, metabolic response correlated with objective response but not with survival. 8, 21, 22 So far, to our knowledge, no data on the effect of EGFR-blockade are available.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal cancer is the world's third most common malignancy and the second leading cause of cancer-related ORIGINAL ARTICLE Role of 18 4 Associate Professor & PMO 5 Medical Officer-NINMAS Correspondence Address: Dr. Papia Akhter, Assistant Professor, NINMAS, Block-D, BSMMU, Shahbag, Dhaka-1000…”
Section: Introductionmentioning
confidence: 99%